Study on Ground Collapse of Covered Karst Soil Caves by Sudden Drop of Groundwater - Xuejun Chen; Ruijian Guo; Lingming Tang; Xiaochen Zhang (Advances in Civil Engineering)
In this study, the ellipsoidal soil cave with vertical collapses in the covering karst area is studied. Based on certain assumptions, the mechanical model of karst collapse caused by groundwater drop was established. Then, based on the negative pressure calculation formula of soil cave cavity according to Boyle–Mariotte’s law, the expression of the stability coefficient of the soil cave was proposed. Subsequently, the feasibility of the theoretical formula was verified. The calculation example analyzed the relationship of groundwater parameters and overburden thickness. The results show that when the initial groundwater level is higher than the top of cave, the law between the stability coefficient of soil cave and groundwater drawdown shows the jumping horizontal broken line. Thus, soil cave tends to collapse when the falling groundwater level drops over the vault; when the initial groundwater level ranges from the bottom to the top of the cave body, the stability coefficient and groundwater drawdown show a negative correlation law, the curve is steep at the early stage and then becomes gentle at the latter stage, and the higher the initial groundwater level in the cave is, the greater stability coefficient of soil cave reduces; when the initial groundwater level is lower than the bottom of the cave, the effect of drawdown is limited. In addition, for the small drawdown or low initial groundwater level, the stability coefficient of soil cave first decreases and then increases with the increases in thickness of overburden, and the thinner the overburden is, the greater the drawdown rate is; when the drawdown or the initial groundwater level is higher, the stability coefficient of soil cave positively relates to the thickness of the overburden layer.